2016
DOI: 10.1371/journal.pone.0166826
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Body Representation of Obese Children and Adolescents before and after Weight-Loss Treatment in Comparison to Normal-Weight Children

Abstract: ObjectiveThe aim of the study was to investigate whether obese children and adolescents have a disturbed body representation as compared to normal-weight participants matched for age and gender and whether their body representation changes in the course of an inpatient weight-reduction program.MethodsSixty obese (OBE) and 27 normal-weight (NW) children and adolescents (age: 9–17) were assessed for body representation using a multi-method approach. Therefore, we assessed body size estimation, tactile size estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 42 publications
1
28
1
Order By: Relevance
“…There are similar patterns concerning other aspects of body image between individuals with obesity and with anorexia nervosa as well: Recent studies examining body image in individuals with obesity found evidence that obese individuals are not generally biased in estimating their own body size but cognitive-affective factors are likely to play an important role (33). Obese children and adolescents did also not differ in their body size estimation from normal weight children and adolescents (34). To the best of our knowledge, possible common mechanisms have still to be determined.…”
Section: Discussionmentioning
confidence: 92%
“…There are similar patterns concerning other aspects of body image between individuals with obesity and with anorexia nervosa as well: Recent studies examining body image in individuals with obesity found evidence that obese individuals are not generally biased in estimating their own body size but cognitive-affective factors are likely to play an important role (33). Obese children and adolescents did also not differ in their body size estimation from normal weight children and adolescents (34). To the best of our knowledge, possible common mechanisms have still to be determined.…”
Section: Discussionmentioning
confidence: 92%
“…A number of recent studies have reported disruption of tactile distance perception in clinical disorders (e.g., Keizer et al., 2011, 2012; Scarpina et al., 2014; Spitoni et al., 2015; Mölbert et al., 2016; Engel and Keizer, 2017). For example, Keizer and colleagues (Keizer et al., 2011, 2012) found that in comparison with healthy controls, patients with anorexia nervosa overestimated tactile distances on both the belly and hand.…”
Section: Integration Of Tactile Information With Representations Of Bmentioning
confidence: 99%
“…Childhood overweight and obesity are increasing globally, with adverse physical and psychosocial consequences on health and quality of life [1]. Body image-or the perception and thoughts about one's body-has been reported as one of the main factors related to psychological well-being that are more seriously compromised in obesity [2,3]. Moreover, body dissatisfaction seems to increase with overweight status [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, body dissatisfaction seems to increase with overweight status [2,4]. Although weight loss and improved body appearance could represent primary motivators for Physical Activity (PA) in obese children [5], it is still unclear whether weight loss might induce changes in the body representation of obese children [3]. In particular, it is still unclear whether Sustainability 2020, 12, 1128 2 of 13 low levels of PA are determinants or consequences of body dissatisfaction [6].…”
Section: Introductionmentioning
confidence: 99%